Crisis communication : case studies and lessons learned from international disasters - Brataas, Kjell (Routledge, 2018)
"Crisis Communication is an in-depth examination of recent tragedies and natural disasters that have occurred around the globe. The book covers three types of incidents: natural catastrophes, accidents and terror attacks. It focuses on the communication aspect of each incident and provides accounts from people handling the event. Each chapter offers a detailed description of the event and supplementary facts and ilustrace from a variety of sources. With a focus on critical communication elements and lessons learned, Brataas offers valuable advice - based on personal experience with natural disasters, accidents and terror attacks - on some of the most effective ways to prepare for and deal with a crisis. Topics range from interview situations and social media to victim support and active shooter events. This book will be invaluable to those working in public relations and communications, as well as to those working with human resources and general management."- Resumé vydavatel